Cardiac Stem Cell Therapy: Stemness or Commitment?. Issue 1 (January 2013) - Mehta, Ashish; Shim, Winston
Cardiac stem cell therapy to promote engraftment of de novo beating cardiac muscle cells in cardiomyopathies could potentially improve clinical outcomes for many patients with congestive heart failure. Clinical trials carried out over the last decade for cardiac regeneration have revealed inadequacy of current approaches in cell therapy. Chief among them is the choice of stem cells to achieve the desired outcomes. Initial enthusiasm of adult bone marrow stems cells for myocyte regeneration has largely been relegated to paracrine-driven, donor cell-independent, endogenous cardiac repair. However, true functional restoration in heart failure is likely to require considerable myocyte replacement. In order to match stem cell application to various clinical scenarios, we review the necessity to preprime stem cells towards cardiac fate before myocardial transplantation and if these differentiated stem cells could confer added advantage over current choice of undifferentiated stem cells. We explore differentiation ability of various stem cells to cardiac progenitors/cardiomyocytes and compare their applicability in providing targeted recovery in light of current clinical challenges of cell therapy.